Multiplatform application to support the comprehensive geriatric assessment - Cunha, Fábio Danilo Pinhal (2020)
The Comprehensive Geriatric Assessment (CGA) is a multidisciplinary diagnostic tool that assesses older people in five main areas: clinical, physical, mental, functional and social. To apply the CGA, the clinicians must answer a wide range of questions and may use paper-based instructions to guide them. In a previous work related to this dissertation, a mobile application was developed to function as a pocket guide, instead of paper. The app, Geriatric Helper, existed in native versions for Android and iOS. In this work, we reengineered the existing application to use a multiplatform approach based on React Native. In addition to the smartphone versions, a web version has also been introduced, with added features. The functional prototypes (Android, iOS, web) are able to support the realization of CGA, although they still need to be validated in a pilot usage period, before opening to the community.